Mixed monolayer of DPPC and lysine-based cationic surfactants an investigation into the antimicrobial activity - Colomer, Aurora (Langmuir : the ACS journal of surfaces and colloids, 2013)
In this paper, we report studies which aim to elucidate the mechanisms involved in the antimicrobial activity of three cationic lysine-based surfactants: LLM, LALM, and C6 (LL)2. To this end, a simple membrane model (i.e., 1,2-dipalmitoyl-sn-phosphatidylcholine, DPPC) was used to explore the monolayer properties at the air/liquid interface. Compression π-A isotherms of mixtures of DPPC/lysine surfactants at different pH showed an expansion of the DPPC monolayer, suggesting cationic lysine surfactant/DPPC interactions, which strongly depend on surfactant structure and hydrophobic interactions. Antimicrobial activity of the three surfactants has also been assessed with transmission electron microscopy, observing the effects on Staphylococcus aureus and Escherichia coli . The three surfactants caused various kinds of damage to the bacteria tested, such as structural alterations, leakage of internal material, and cell destruction